What Can You Do With a Bachelor's in Public Health? A Case Study of Graduate Outcomes From the University of Hawai‘i - Nelson-Hurwitz, Denise C.; Tagorda, Michelle; Kehl, Lisa; Patil, Uday (Frontiers in Public Health, 2021)
Since the development of a Bachelor of Arts in public health, a common question among prospective students, faculty, and community members has been asked: “What will students do after graduation?” While national data on graduates are abundant, community inquiries sought more detailed profiles of local graduates. To address this need, data on 224 graduates of the Bachelors of Arts in Public Health (BAPH) degree at the University of Hawai‘i at Mānoa were collected through alumni outreach efforts and professional online profile searches. Data were compiled into a summary presentation and program ‘resume’. Findings indicated roughly 30% of BAPH graduates pursued graduate-level education and 43% were employed within a year of graduation. Employment in local NGOs and healthcare organizations was common, while bureaucratic challenges limited hiring at public agencies. A review of job titles suggested graduates were employed in program coordination or support staffing. Local program profiles, such as this one, complement national employment data. Moreover, these efforts may foster interest among prospective students and support from faculty, administrators, and employers.